Relation between hypomethylation of long interspersed nucleotide elements and risk of neural tube defects - Wang, Li; Wang, Fang; Guan, Jing; Le, Jing; Wu, Lihua; Zou, Jizhen; Zhao, Huizhi; Pei, Lijun; Zheng, Xiaoying; Zhang, Ting (The American journal of clinical nutrition, 2010)
BACKGROUND: Impaired one-carbon metabolism is thought to be associated with the risk of neural tube defects (NTDs); however, the role of methylation in NTDs remains unclear. Long interspersed nucleotide element-1 (LINE-1) constitutes 17-25% of the human genome. LINE-1 hypomethylation correlates with global DNA methylation levels in cancerous cells, but limited information is available on LINE-1 methylation in NTDs. OBJECTIVE: We determined whether LINE-1 methylation patterns were associated with neural tube development and the possible relations between DNA methylation and key maternal metabolites involved in folate-mediated one-carbon metabolism. DESIGN: Global methylation, maternal plasma folic acid, vitamin B-12, and total homocysteine (tHcy) concentrations were assessed in 48 NTD and 49 control samples by immunoassay, and LINE-1 methylation levels were evaluated by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. RESULTS: Methylation levels of genomic DNA and LINE-1 decreased significantly in the neural tissue of NTD samples. The risk of NTDs increased with decreasing levels of LINE-1 methylation, with an odds ratio of 5.246 (95% CI: 1.519, 18.124; P = 0.009) for the lowest quartile (methylation level [less-than or equal to] 57.94%) compared with the highest quartile (methylation level ≥ 60.94%). Compared with control subjects, case subjects had lower maternal plasma concentrations of vitamin B-12. CONCLUSIONS: Hypomethylation of LINE-1 and genomic DNA was associated with an increased risk of NTDs. Functional insufficiency of maternal plasma vitamin B-12 was associated with NTDs, although no significant correlation could be established between maternal folic acid, vitamin B, tHcy, and LINE-1 methylation.